Measuring Digital Inequality in Australia: the Australian Digital Inclusion Index - Wilson, Chris K; Thomas, Julian; Barraket, Jo (Journal of Telecommunications and the Digital Economy, 2019)
In the past two decades digital inequality has come to be understood as a complex, evolving and critical issue in Australia, as it has elsewhere. This conceptual shift has generated demand for more complex measurement tools that can capture and combine multiple and graduated indicators of digital inequality. The Australian Digital Inclusion Index (ADII), developed in 2015 and now including annual data covering the period 2014 to 2018, is a composite index that addresses this demand. This paper describes the development of the ADII, its architecture and the dataset used to populate it. It also provides an overview of the findings of the 2018 edition of the index. The 2018 index reveals that, although on aggregate digital inclusion is improving in Australia, it continues to follow distinct geographic, social and socio-economic contours. In general, rural and regional Australians, older Australians and Australians with low levels of income, employment, and education are less digitally included than their compatriots. For some of these groups the inclusion gap is widening.